The Use of Small Capital Selling Snacks as A Business Opportunity in The Langowan Shopping Complex - Sumampouw, Olviane Olke (Asia Pacific Journal of Management and Education (APJME), 2021)
Langowan is a strategic center of economic activity because it is a meeting place for several sub-districts in Minahasa and Mitra. Therefore, the authors see a market opportunity to start a business selling snacks, including selling wet and dry cakes in the Langowan shopping complex. By considering the research objectives that have been set, this research tends to use the "the out-side in" or "opportunity recognition" approach, which is an approach that emphasizes the idea of responding to market needs as the key to success. Based on the "in-side out" approach, to start a business, a prospective entrepreneur must have business competence.